Guwiyang Wurra–'Fire Mouse': a global gene knockout model for TSPO/PBR drug development, loss-of-function and mechanisms of compensation studies. (3rd August 2015) - Middleton, Ryan J.; Liu, Guo-Jun; Banati, Richard B.
Abstract : The highly conserved 18-kDa translocator protein (TSPO) or peripheral benzodiazepine receptor (PBR), is being investigated as a diagnostic and therapeutic target for disease conditions ranging from inflammation to neurodegeneration and behavioural illnesses. Many functions have been attributed to TSPO/PBR including a role in the mitochondrial permeability transition pore (MPTP), steroidogenesis and energy metabolism. In this review, we detail the recent developments in determining the physiological role of TSPO/PBR, specifically based on data obtained from the recently generated Tspo knockout mouse models. In addition to defining the role of TSPO/PBR, we also describe the value of Tspo knockout mice in determining the selectivity, specificity and presence of any off-target effects of TSPO/PBR ligands.